Enhancing two-dimensional perovskite photodetector performance through balancing carrier density and directional transport. Issue 39 (20th September 2022) - Huang, Tao; Zhu, Zhicheng; Zhao, Chen; Kong, Wenchi; Chen, Xuhang; Li, Ruiyan; Yu, Zhi; Shi, Zhiming; Li, Dabing; Yang, Bai; Yu, Weili
Abstract : A balance between carrier density and carrier directional transport is achieved when the inorganic layer number n is 4, and thereby a high-efficiency perovskite single crystal horizontal photodetector is prepared. Abstract : Recently, two-dimensional (2D) Ruddlesden–Popper perovskites have attracted extensive attention in the research society owing to their unique organic and inorganic layered structure induced superb stability. However, the quantum confinement effect and dielectric confinement effect caused by the layered structure of 2D perovskites limit the carrier transport and further hinder performance improvement of 2D perovskite optoelectronic devices. To resolve this problem, we have adjusted carrier density and carrier lateral transport in 2D perovskites by a layer optimization strategy. A series of 2D perovskite PEA2 MA( n −1) Pb n I3 n +1 single crystals with varying layers ( n = 1–5) have been synthesized by an in situ reverse temperature crystallization procedure, and ultra-high efficiency lateral structured photodetectors have been achieved. When n is 4, the photodetector shows the highest responsivity of 3077 A W −1 which is over 20 times higher than previous reports. A record external quantum efficiency of 7.2 × 10 6 % is also achieved. The density functional theory calculations also confirm that directional migration of perovskite carriers is optimal when the layer number of the 2D perovskite PEA2 MA( n −1) Pb n I3 n +1 is 4. This research shows that the layer number n is a key parameter in tuning the carrier density and lateral transport properties of the 2D PEA2 MA( n −1) Pb n I3 n +1 perovskite, and a balance between these two parameters can be achieved when n is 4. This work is instructive for the fabrication of high-performance 2D perovskite optoelectronic devices.